Weighting in sequence space: a comparison of methods in terms of generalized sequences. - Martin Vingron; Peter R. Sibbald (1993)
Four methods for weighting aligned biological sequences have recently appeared that differ mathematically, philosophically, and in their results. Thus, while there is consensus about the need to weight sequences, the method to use is contentious. A geometric analysis based on a continuous sequence space is presented that provides a common framework in which to compare the methods. It is concluded that there are two "best" methods. When the sequences are known to be phylogenetically related and a tree can be generated without introducing excessive stress into the data, the method of Altschul et al. [Altschul, S. F., Carroll, R. J. & Lipman, D. J. (1989) J. Mol. Biol. 207, 647-653] is appropriate. When the sequences are not known to be phylogenetically related or a tree cannot be produced without unduly distorting the distances between the sequences, a modification of the method of Sibbald and Argos [Sibbald, P. R. & Argos, P. (1990) J. Mol. Biol. 216, 813-818] is preferable.